Sinergi Pengabdian Akademisi Dalam Penguatan Perencanaan Infrastruktur Sebagai Narasumber Pembanding Pada Forum Perangkat Daerah - Dermawan Zebua; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The involvement of academics in regional development planning is a tangible implementation of the university's community service mission under the Tri Dharma of Higher Education. This community service activity aimed to strengthen regional infrastructure development planning through the role of academics as resource persons and technical reviewers in the Regional Government Work Plan (RKPD) Forum of Gunungsitoli City for the 2027 planning year. The activity employed a participatory assistance approach by providing technical input, evaluation, and recommendations on development programs proposed by Regional Government Organizations (Organisasi Perangkat Daerah/OPD). The implementation consisted of four stages: preparation, forum implementation, technical recommendation delivery, and evaluation. The results demonstrated that academic participation contributed positively to improving the quality of regional planning documents, particularly in road infrastructure, drainage systems, clean water supply, solid waste management, public building development, disaster risk mitigation, and sustainable infrastructure planning. Interactive discussions between academics and local government agencies generated evidence-based technical recommendations that were considered in refining the 2027 RKPD. Furthermore, the activity strengthened collaboration between higher education institutions and the Government of Gunungsitoli City in promoting participatory, evidence-based, and community-oriented development planning. Therefore, the role of academics as technical reviewers in the Regional Government Work Plan Forum proved effective in enhancing the quality of regional development planning and supporting sustainable, resilient, and efficient infrastructure development.